COVID- 19 and abnormalities of some biochemical tests: review - Alaa Shawqi Abdulbari; Noor N. O. Al-Saadi (Qubahan Academic Journal)
Coronaviruses are a group of viruses proven to affect both respiratory and gastrointestinal diseases in varied animal and human organisms. More than 100 million people worldwide are currently believed to have been infected and more than two million people have died and induced clinical syndrome of coronavirus disease in 2019.It's (COVID-19).